Mannose-Binding Lectin Gene Polymorphism versus Microbial Virulence in the Pathogenesis of Vulvovaginal Candidiasis and Recurrent Vulvovaginal Candidiasis - Wali, Iman; Haggag, Eman M.; Awad, Alaa R.; El-Sharkawy, Mohammad A.; Sallam, Marwa K. (Open Access Macedonian Journal of Medical Sciences, 2023)
BACKGROUND: Vulvovaginal candidiasis (VVC) is one of the most common infections affecting women. AIM: This study aimed to determine MBL2 polymorphism frequency among females with VVC together with assessment of Candida virulence attributes in the pathogenesis of it. METHODS: Fifty Egyptian patients and 50 controls were included in the study. Vaginal swabs were cultured to identify Candida spp. D-ARMs were used to determine MBL2 polymorphism. RESULTS: Cases with VVC revealed Candida albicans 37(74%) and non-Albicans Candida (NAC) 13 (26%) with a significant difference between C. albicans and NAC esterase and phospholipase. Thirty C. albicans isolates (81.1%) possessed three or more virulence factors, compared to only four NAC (30.8%) (p = 0.002). As regards MBL2 polymorphism, the X allele was found to be significantly high in cases than in controls (p ≤ 0.001). B allele on codon 54 and L allele on promoter region was more in cases. Other haplotypes were more in cases than controls with a significant difference for LXQB and HXQB. HXPB and LXQB were detected among recurrent VVC (RVVC) cases more than VVC cases. CONCLUSION: RVVC appears to be a multi-factorial disorder; hence, treatment should be individualized. Recombinant MBL may be considered in the future treatment of RVVC in the case of associated genetic MBL2 polymorphism.